(untitled) (E Global Congress, 2024)
The global prevalence of COVID-19 and chronic fatigue syndrome (CFS) highlights the substantial health burden these conditions pose individually and in combination. COVID-19, caused by SARS-CoV-2, continues to affect millions worldwide, with post-acute sequelae, known as Long COVID, impacting an estimated 5-43% of recovered individuals. Among these, chronic fatigue is a prominent and persistent symptom, with 42.5% of Long COVID patients experiencing fatigue that can resemble CFS. Chronic fatigue syndrome (CFS), affecting an estimated 0.4% to 2.5% of the global population, is marked by enduring, debilitating fatigue often triggered by infections. Emerging data suggest that SARS-CoV-2 may exacerbate or reveal latent CFS-like symptoms, linking these conditions biologically and symptomatically. Given the shared features of immune dysregulation and fatigue in both conditions, this paper reviews their epidemiological profiles and underscores the need for enhanced diagnostic criteria, research, and support systems. Improved understanding of these overlapping syndromes is crucial for global health strategies to mitigate their societal and economic impacts.